Effect of Hydroalcoholic Extract of Hypericum Perforatum L. Leaves on Ethylene Glycol-Induced Kidney Calculi in Rats - Khalili, Mohsen; Jalali, Mohammad Reza; Mirzaei-Azandaryani, Mohammad (Urology Journal, 2012)
PURPOSE: To investigate the effects of the hydroalcoholic extract of Hypericum perforatum (H. perforatum) leaves on the kidney calculi in rats. MATERIALS AND METHODS: Fifty-two Wistar male rats were randomly divided into 4 groups: Groups 2, 3, and 4 received ethylene glycol (EG) 1% + ammonium chloride (0.5%)-added drinking water as a stone inducer. The H. Perforatum solution was fed at the same time of EG application and was repeated once for two days until the end of the experimental period. Group 1 (control; n = 10) was provided free access to food and normal drinking water. Group 2 (EG; n = 12) received EG-ammonium chloride-added drinking water and was fed with normal chow. Groups 3 and 4 (n = 15), as EG-treatment groups, received H. Perforatum in low (300 mg/kg) and high (500 mg/kg) doses, respectively. After 28 days, the kidneys were removed and prepared for histologic evaluation of calcium oxalate deposits. RESULTS: Urine level of free calcium in groups EG and EG + H. perforatum (300 mg/kg) and phosphorous in EG + H. perforatum (500 mg/kg) significantly decreased compared to controls (P < .01; P < .05; and P < .05, respectively). Treatment of the rats with high dose of H. Perforatum (500 mg/kg) markedly reduced decrementing effect of EG on serum level of free calcium (P < .05). Histological experiments showed that chronic feeding of H. perforatum (300 and 500 mg/kg, orally) could significantly reduce the size and number of calcium oxalate deposits in EG group. CONCLUSION: Chronic treatment of rats with hydroalcoholic extract of H. perforatum reduced the size and number of calcium oxalate deposits in EG-induced calculi.